2008
DOI: 10.1084/jem.20081297
|View full text |Cite
|
Sign up to set email alerts
|

TSC–mTOR maintains quiescence and function of hematopoietic stem cells by repressing mitochondrial biogenesis and reactive oxygen species

Abstract: A long-standing but poorly understood observation in stem cell biology is that the quiescence of the adult stem cells associates with their longterm functions ( 1 -6 ). The molecular pathway that keeps them in quiescence is largely obscure, although recent studies have implicated stem cell niches ( 4 ) and cell-intrinsic functions of p21 ( 5 ) and Pten ( 6 ) in this process. The signifi cance of quiescence in stem cell function is bolstered as genetic disruption of its quiescence almost invariably inactivates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
514
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 626 publications
(564 citation statements)
references
References 49 publications
34
514
0
5
Order By: Relevance
“…In contrast, other studies have suggested roles for ROS in depletion of TSC1-deficient HSCs. 186 In these studies, TSC-1 depletion causes mTOR activation, exit from quiescence, increased proliferation, but leads to exhaustion of HSCs without the development of leukemia.…”
Section: Mtorc1-hif Drug Resistancementioning
confidence: 99%
“…In contrast, other studies have suggested roles for ROS in depletion of TSC1-deficient HSCs. 186 In these studies, TSC-1 depletion causes mTOR activation, exit from quiescence, increased proliferation, but leads to exhaustion of HSCs without the development of leukemia.…”
Section: Mtorc1-hif Drug Resistancementioning
confidence: 99%
“…Interestingly, pretreatment of aged mice with rapamycin, which inhibits mTOR activity, rescues many of the functional defects observed in old HSCs, including their decreased cell cycle activity and diminished engraftment . At the moment it is quite challenging to integrate this observation with the aforementioned increase in p16 Ink4a expression exhibited by the old HSCs because increased mTOR activity results in increased HSC cycling, at least in young Pten / and Tsc1 / HSCs (Yilmaz et al, 2006;C. Chen et al, 2008).…”
Section: Aging and The Control Of Hsc Cell Cycle Activitymentioning
confidence: 99%
“…As described previously, mouse models that lead to unchecked levels of mTOR activity result in a deregulated HSC compartment and stem cell exhaustion (Yilmaz et al, 2006;Zhang et al, 2006;C. Chen et al, 2008).…”
Section: Aging and The Control Of Hsc Cell Cycle Activitymentioning
confidence: 99%
“…Therefore, retaining functional TSC1/2‐mTORC1 regulation may be beneficial for certain cancer cells (Mieulet & Lamb, 2010). An important role of TSC1/2 in metabolic homeostasis was revealed in hematopoietic stem cells (HSCs) where deletion of TSC1 results in elevated mTORC1 activity and increased ROS production with detrimental effects on HCS function and survival (Chen et al , 2008). A database survey revealed that TSC1 ‐mRNA expression is the highest in Burkitt's lymphoma‐derived cell lines compared to 36 different tumor‐type cell lines in the Cancer Cell Line Encyclopedia (CCLE; http://www.broadinstitute.org/ccle) (Fig EV1A).…”
Section: Introductionmentioning
confidence: 99%